Use of a Convex Pouching System in the Postoperative Period: A National Consensus. Issue 3 (May 2022) - Colwell, Janice C.; Stoia Davis, Janet; Emodi, Krisztina; Fellows, Jane; Mahoney, Mary; McDade, Bethany; Porten, Sima; Raskin, Elizabeth; Sims, Terran; Norman, Holly; Kelly, Matthew T.; Gray, Mikel
Abstract : Convex pouching systems have been available for ostomy patients for decades; however, controversy remains over the use of convexity in the postoperative period. A group of 10 nurses and physicians with expertise caring for patients with an ostomy completed a scoping review identifying research-based evidence and gaps in our knowledge of the safety and effectiveness related to the use of a convex pouching system following ostomy surgery. Results of this scoping review demonstrated the need for a structured consensus to define best practices when selecting a pouching system that provides a secure and reliable seal around the stoma, avoids undermining and leakage of effluent from the pouching system, and contributes to optimal health-related quality of life for patients following ostomy surgery. The expert panel reached consensus on 8 statements for the use of convex products immediately after surgery and throughout the first 6 months after stoma creation, as well as describing goals in choosing the best pouching system for the patient with an ostomy.